Unanswered questions in the regulation and function of the duplicated α7 nicotinic receptor gene CHRFAM7A - Sherry Leonard; Roberta Benfante (Elsevier, 2023)
The α7 nicotinic receptor (α7 nAChR) is an important entry point for Ca2+ into the cell, which has broad and important effects on gene expression and function. The gene (CHRNA7), mapping to chromosome (15q14), has been genetically linked to a large number of diseases, many of which involve defects in cognition. While numerous mutations in CHRNA7 are associated with mental illness and inflammation, an important control point may be the function of a recently discovered partial duplication CHRNA7, CHRFAM7A, that negatively regulates the function of the α7 receptor, through the formation of heteropentamers; other functions cannot be excluded. The deregulation of this human specific gene (CHRFAM7A) has been linked to neurodevelopmental, neurodegenerative, and inflammatory disorders and has important copy number variations. Much effort is being made to understand its function and regulation both in healthy and pathological conditions. However, many questions remain to be answered regarding its functional role, its regulation, and its role in the etiogenesis of neurological and inflammatory disorders. Missing knowledge on the pharmacology of the heteroreceptor has limited the discovery of new molecules capable of modulating its activity. Here we review the state of the art on the role of CHRFAM7A, highlighting unanswered questions to be addressed. A possible therapeutic approach based on genome editing protocols is also discussed.